Efforts to Improve Writing Procedure Ability Using Cooking Video In Second Class Students of SMAN 1 Jakenan - Ulfa Hanim Safitri (Jurnal Pendidikan Indonesia, 2021)
The objectives of the study are 1) to find out the students’ writing ability in procedure text of the twelfth grade students at SMA N 1 Jakenan who are taught with cooking video by “Master Chef Australia” as teaching media. 2) to find out the students’ writing ability in procedure text of the twelfth grade students at SMA N 1 Jakenan who are taught without cooking video by “Master Chef Australia” as teaching media. 3) to find out the significant differences of the students’ writing ability in procedure text of the twelfth grade students at SMA N 1 Jakenan who are taught with cooking video by “Master Chef Australia” as teaching media and those who are taught without cooking video by “Master Chef Australia” as teaching media. In this research, the researcher used quantitative method. The design of this research was pre - experimental design. The researcher took the sample at SMA Negeri 1 Jakenan in solving the problem. Furthermore, the researcher used test to collect the data. In this research, the researcher chose XII MIPA 4 class as the sample. Based on the result, the mean score of pre-test was 60.33 and mean score of post-test was 79.75. Finally the result of the data analysis of the ttest was 11.622. From the ttable of significances 5% with df = 35 was 2.0390 Then, the ttest was higher than ttable(11.622 > 2.030). Therefore, the working hypothesis (Ha) is accepted and the nul hypothesis (Ho) is rejected. It means that the use of cooking video by “Master Chef Australia” can be accepted. In other words, it is effective to improve the students’ writing ability in Procedure Text. It is suggested that teacher can apply this method to improve students’ writing ability in Procedure Text.